COMPARATIVE STUDY OF RACEMIC SALBUTAMOL AND LEVOSALBUTAMOL IN PATIENTS WITH BRONCHIAL ASTHMA - DR.RAADHIKA.K,; DR.SHANTHI.M, (International Journal of Pharma and Bio Sciences, 2012)
To compare the efficacy and tolerability of oral racemic salbutamol and levosalbutamol in patients with mild bronchial asthma. a single blind trial was designed to find out the usefulness of the tablet racemic salbutamol (2mg) and levosalbutamol (1mg) given independently to 25 matched mild bronchial asthma cases who satisfied a rigid inclusion and exclusion criteria at three times daily dosage over a period of 15 days. They were assessed objectively before and after by peak flow meter and serum potassium; and subjectively by palpitation, cough, breathlessness, and wheeze. Data were analysed statistically. The mean peak expiratory flow rate before and after therapy in racemic salbutamol group was 227.50 and 248ml respectively and in levosalbutamol group 231 and 282.5ml respectively with significant improvement in both but more in latter. No significant difference in serum potassium level either in intra or in inter group was noticed. Tachycardia, tremor, and muscular cramps were significantly low in levosalbutamol group. Levosalbutamol was found to be superior to salbutamol in terms of efficacy and tolerability in patients with mild bronchial asthma as evidenced by subjective and objective means.